2005
DOI: 10.1890/04-0076
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Effects of Flood Control on a Flood‐dependent Riparian Forest

Abstract: The downstream effects of dams on riparian forests are strongly mediated by the character and magnitude of adjustment of the fluvial-geomorphic system. To examine the effects of flow regulation on sand-bed streams in eastern Colorado, we studied the riparian forest on three river segments, the dam-regulated South Fork Republican River downstream of Bonny Dam, the unregulated South Fork Republican River upstream of Bonny Dam, and the unregulated Arikaree River. Although Bonny Dam significantly reduced peak and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 49 publications
0
35
1
Order By: Relevance
“…The larger size of Russian olive individuals in the open could have been due either to earlier establishment in these areas or to faster growth there. However, Katz et al (2005) found no evidence that Russian olive had established earlier in open habitats than in the cottonwood understory in our study area. Thus, the larger size of Russian olive individuals in the open was likely due to faster growth rates where light levels were 1.5 times higher than under the cottonwood canopy.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The larger size of Russian olive individuals in the open could have been due either to earlier establishment in these areas or to faster growth there. However, Katz et al (2005) found no evidence that Russian olive had established earlier in open habitats than in the cottonwood understory in our study area. Thus, the larger size of Russian olive individuals in the open was likely due to faster growth rates where light levels were 1.5 times higher than under the cottonwood canopy.…”
Section: Discussioncontrasting
confidence: 88%
“…Few other tree or shrub species are present at these sites, and these are only rarely found. For example, Katz et al (2005) found that the next most common tree or shrub at our sites, Juniperus virginiana L., represented only 0.6% of the individual trees or shrubs present in the study area. At each site, Russian olive stands extended at least 100 m away from the river and at least 400 m along the river's length.…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…According to Katz et al (2005), in the North American Great Plains, dams typically have reduced both downstream peak discharge and sediment load, resulting in diminished stream power downstream and a narrower active river channel. When dams retain sediment and reduce discharge, in the long term, there is a reduction in the channel migration rate because those flows able to produce erosion and point bar deposition are no longer released (Friedman et al, 1998;Johnson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the North American Great Plains (Katz et al, 2005), dams typically have reduced both downstream peak discharge and sediment load, resulting in diminished stream power downstream and a narrower active river channel. When dams retain sediment and reduce discharge, in the long term, there is a reduction in the channel migration rate because those flows able to produce erosion and point bar deposition are no longer released (Friedman et al, 1998;Johnson, 1998).…”
Section: Introductionmentioning
confidence: 99%